ANALYSIS OF THE FACTORS AFFECTING RUBBER EXPORT VOLUMES NATURAL INDONESIA TO FIVE DESTINATION COUNTRIES - Eliza Vivi Nurzila; Anak Agung Ketut Ayuningsasi (Adisam Publisher, 2024)
Rubber is one of the non-oil and gas export commodities or plantations which plays a very important role in the Indonesian economy and is also one of the non-oil and gas commodities which contributes quite a large amount of foreign exchange.This research was conducted with the aim of analyzing the factors that influence the volume of Indonesian natural rubber exports to five destination countries, namely exchange rate, production amount, land area, international prices, GDP per capita of destination countries, and economic distance. This research was conducted in several destination countries, namely the United States, Japan, India, China and South Korea, which are the main destination countries for Indonesian natural rubber exports, because the volume of Indonesian natural rubber exports to these countries is the highest among several other countries. This research data is in the form of time series and cross section secondary data using annual data starting from the 2010 period to the 2022 period obtained from Central Statistics Agency, Directorate General of Indonesian Plantations, Export Commodity Analysis, Indexmundi, world bank, Center for Prospective Studies and International Information (CEPII), as well as related articles and journals. This research uses a data collection method, namely non-participant observation. The data analysis technique in this research is panel data regression analysis using Eviews 12 software. The results of this research show that exchange rates have a negative and significant effect on Indonesian natural rubber in the five destination countries. The amount of production has a positive and significant effect on Indonesian natural rubber in the five destination countries. Land area does not have a significant effect on Indonesian natural rubber in the five destination countries. International prices do not have a significant effect on Indonesian natural rubber in the five destination countries. GDP per capita of the destination country has a positive and significant effect on Indonesian natural rubber in the five destination countries. Economic distance has a negative and significant effect on Indonesian natural rubber to the five destination countries.